Titanized or Zirconized Porous Silica Modified with a Cellulose Derivative as New Chiral Stationary Phases - You Jin Seo; Gyoung Won Kang; Seong Tae Park; 문명희; 박정학; Won Jo Cheong (Bulletin of the Korean Chemical Society, 2007)
Spherical porous silica supports modified with titanium or zirconium alkoxides were prepared, and allyl groups were chemically attached to the titanized or zirconized silica supports, and the product was cross-polymerized with a double bond containing cellulose derivative to yield new CSPs (chiral stationary phases). Magic angle spinning 13C solid state NMR and elemental analysis were used to characterize the CSPs. The performances of the chiral stationary phases were examined in comparison with a conventional chiral stationary phase. Spherical porous silica particles modified with 3,5-dimethylphenylcarbamate of cellulose were prepared and used as the conventional chiral stationary phase. Chromatographic data were collected for a few pairs of enantionmers in heptane/2-propanol mixed solvents of various compositions with the three chiral columns and the results were comparatively studied. The separation performance of the chrial phase made of the titanized silica was better than the others, and the separation performance of the chiral phase of the zirconized silica was comparable to that of the conventional chiral phase. The superiority of titanized silica over bare or zirconized silica in chiral separation seemed to be owing to the better yield of crosslinking (monitored by increase of carbon load) for titanized silica than for the others. KCI Citation Count: 10